2015
DOI: 10.1186/s12889-015-1904-1
|View full text |Cite
|
Sign up to set email alerts
|

Reliable mortality statistics for Turkey: Are we there yet?

Abstract: BackgroundThe Turkish government has implemented several reforms to improve the Turkish Statistical Institute Death Reporting System (TURKSTAT-DRS) since 2009. However, there has been no assessment to evaluate the impact of these reforms on causes of death statistics. This study attempted to analyse the impact of these reforms on the TURKSTAT-DRS for Turkey, and in the case of Izmir, one of the most developed provinces in Turkey.MethodsThe evaluation framework comprised three main components each with specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 13 publications
0
19
0
5
Order By: Relevance
“…Around four decades ago, an international evaluation suggested that countries paid attention to vital statistics programmes at a stage in their economic development where such data were imperative for policy 72. These factors probably influenced improvements in national CRVS systems in Turkey, Oman and the Philippines in recent times 73–75. Moreover, the advent of computerisation has vastly enhanced the potential for greater efficiencies in data management.…”
Section: Resultsmentioning
confidence: 99%
“…Around four decades ago, an international evaluation suggested that countries paid attention to vital statistics programmes at a stage in their economic development where such data were imperative for policy 72. These factors probably influenced improvements in national CRVS systems in Turkey, Oman and the Philippines in recent times 73–75. Moreover, the advent of computerisation has vastly enhanced the potential for greater efficiencies in data management.…”
Section: Resultsmentioning
confidence: 99%
“…The mortality due to sICH was reported to be lower in Japan than in any other region [ 1 ], and this might result from an intensive medical intervention attitude even for comatose patients with sICH [ 12 ]. Further, we should be skeptical about the accuracy of the reported mortality number, since this also definitely contains errors due to misdiagnosis [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Takođe, pouzdani i validni podaci o mortalitetu su važni za epidemiološka istraživanja kao i za javno-zdravstvenu politiku i prioritetne ciljeve [6]. Statistika mortaliteta je jedan od osnovnih izvora zdravstvenih informacija i u mnogim zemljama je najpouzdaniji izvor zdravstvenih podataka [7].…”
Section: Uvodunclassified